Lipoteichoic Acid Is Involved in the Ability of the Immunobiotic Strain Lactobacillus plantarum CRL1506 to Modulate the Intestinal Antiviral Innate Immunity Triggered by TLR3 Activation - Mizuno, Hiroya; Arce, Lorena; Tomotsune, Kae; Albarracin, Leonardo; Funabashi, Ryutaro; Vera, Daniela; Islam, Md. Aminul; Vizoso-Pinto, Maria Guadalupe; Takahashi, Hideki; Sasaki, Yasuko; Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2020)
Studies have demonstrated that lipoteichoic acid (LTA) is involved in the immunomodulatory properties of some immunobiotic lactobacilli. The aim of this work was to evaluate whether LTA contributes to the capacity of Lactobacillus plantarum CRL1506 of modulating the intestinal innate antiviral immune response. A D-alanyl-lipoteichoic acid biosynthesis protein (dltD) knockout CRL1506 strain (L. plantarum ΔdltD) was obtained and its ability to modulate Toll-like receptor (TLR)-3-mediated immune response was evaluated in vitro in porcine intestinal epithelial (PIE) cells and, in vivo in Balb/c mice. Wild-type CRL1506 (L. plantarum WT) was used as positive control. The challenge of PIE cells with the TLR3 agonist poly(I:C) significantly increased IFN-β, IL-6 and MCP-1 expressions. PIE cells pretreated with L. plantarum ΔdltD or L. plantarum WT showed higher levels of IFN-β while only L. plantarum WT significantly reduced the expression of IL-6 and MCP-1 when compared with poly(I:C)-treated control cells. The oral administration of L. plantarum WT to mice prior the intraperitoneal injection of poly(I:C) significantly increased IFN-β and IL-10, and reduced intraepithelial lymphocytes (CD3+NK1.1+CD8αα+) and pro-inflammatory mediators (TNF-α, IL-6 and IL-15) in the intestinal mucosa. Similar to the WT strain, L. plantarum ΔdltD-treated mice showed enhanced levels of IFN-β after poly(I:C) challenge. However, treatment of mice with L. plantarum ΔdltD was not able to increase IL-10 or reduce CD3+NK1.1+CD8αα+ cells, TNF-α, IL-6 or IL-15 in the intestine. These results indicate that LTA would be a key molecule in the anti-inflammatory effect induced by the CRL1506 strain in the context of TLR3-mediated inflammation.